2016
DOI: 10.1007/s11192-016-2139-3
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of ethnic groups to Malaysian scientific output, 1982–2014, and the effects of the new economic policy

Abstract: Malaysia has three main ethnic communities: Chinese, Indians and Malays. At independence in 1957, the Chinese dominated commercial life, and this led to ethnic tensions and finally riots. As a result in 1969 Malaysia introduced a “New Economic Policy” (NEP) to promote Malays in all areas of activity, and in particular to assist them to obtain basic and higher education. We examined the scientific outputs from Malaysia between 1982 and 2014 and classified the names of Malaysian researchers into one of these thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Most of the current study respondents were unmarried reflecting that cadet officers cannot marry whilst a student, but also that most Malaysian university students are unmarried with the average age of marriage being 26–28 years 106,107. Although Malaysia is a multi-ethnic country, Malays are the largest race108 and, reflecting that, the respondents were mostly Malay.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current study respondents were unmarried reflecting that cadet officers cannot marry whilst a student, but also that most Malaysian university students are unmarried with the average age of marriage being 26–28 years 106,107. Although Malaysia is a multi-ethnic country, Malays are the largest race108 and, reflecting that, the respondents were mostly Malay.…”
Section: Discussionmentioning
confidence: 99%
“…The methodological approach has been described in detail elsewhere 14 . The second aspect for specific study was the presence of cancer researchers with one or more of 2400 Russian names (ending in "-enko", "-ev", "-nin", and "-ov" and their feminine equivalents) on non-Russian origin papers, to study migration patterns, as previously described 15 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been established earlier that ethnicity influences warfarin sensitivity. Several studies reported higher incidence of major bleeding among Asian population than in European countries and the US [27][28][29], suggesting that lower doses are needed to achieve the target PT-INR [30]. This might be due to the variability in the biological response to warfarin or the average body mass index, which is considered small for Asian population [16,17].…”
Section: Matalqah Et Almentioning
confidence: 99%